THE INFLUENCE OF HOPE ON THE PRO-SOCIAL CONDUCT OF SECONDARY SCHOOL TEACHERS - Nwosu, Ikenna T; Udeh, Nneka I; Nwankwo, Chijioke A (International Research Journal of Arts and Communication, 2024)
The study investigated hope as a predictor of pro-social behaviour among secondary school teachers, ninety-eight (98) public school teachers comprising 73 females and 27 males with a mean age of 37.61 and S.D of. 7.618 were drawn as participants from public secondary schools in Nkanu West Local Governmental using purposive sampling techniques. Pro-socialness Scale, The Adult Hope Scale was used for data collection, correlational design was adopted, and the statistical test used for data analysis was linear regression using Statistical Package for Social Sciences (SPSS) Version 25 software. Findings revealed that hope (agency Stβ= .301** t= 3.280** at p< .01, pathway Stβ= .349*** t= 4.695*** at p< .001 and filler Stβ= .187* t= 2.255* at p< .05) positively predict pro-social behaviour among school teachers, Hope r= .642 relate to pro-social behaviour, it contributed 41.2 % variance to pro-social behaviour at r2= .412, hope predicted pro-social behaviour at p< .001. Hence school management should come up with a package that can make the teachers to be hopeful, they should also make an effort to encourage their staff this will increase their level of emotional intelligence, and will help to increase hope for pro-social behaviour to be present.